Convergência das normas brasileiras de contabilidade aplicadas ao setor público aos padrões internacionais: análise da evidenciação pelos estados brasileiros e pelo Distrito Federal - Mariana Camilla Coelho Silva Castro (2016)
Accounting has undergone profound changes in order to make it more understandable, reliable and to promote the homogenization of the provided information. In this regard, it began a developing process of international standardization of accounting, including the public sector.In Brazil, in 2008, the first standards were published based on the international patterns. The adoption of international standards can improve the disclosure quality, since the information provided by the financial statements is the main control tool of the public resources use. This study aimed to analyze the characteristics of the Brazilian states and the Federal District that may explain the disclosure level of the changes brought by the Brazilian Accounting Standards Applied to the Public Sector (NBCASP), according to the convergence process to internationalstandards public accounting. The characteristics of public entities analyzed were: Revenue Budget; Federal Funds Transfers to the States; GDP per capita; FIRJAN Index of Municipal Development; and Human Development Index in its three dimensions: Education, Longevityand Income; literacy rate and population. The research sample consisted of 25 Brazilian states in addition to the Federal District, once the Roraima State had not disclosed its financial statements from 2014 to December / 2015, period when the data collection was carried out. The theoretical frame presents discussions about the main changes brought to the national public accounting by the convergence process to the international standard, and the Disclosure Theory as a basis for this study. Nonparametric tests were performed to evaluate the correlation,multiple linear regression analysis, factor analysis and cluster analysis. Empirical evidence showed an average disclosure according to the NBCASP requirements equal to 76%. It demonstrates that the Brazilian states and the Federal District still have much to evolve in terms of disclosure to meet the legal requirements and to provide clear and quality information to citizens in exercising social control. The results of multiple regression analysis allowed to identify the explanatory features of the disclosure index according to NBCASP and to answer the research question of the study. It was observed that the size of the public entities, composed by Revenue Budget, Federal Funds Transfer to States and Population; can be considered an explanatory feature of the ID as the NBCASP at 10%-significance level. It shows that the largest public entities in size have the best disclosure rates. The cluster analysis allowed the classification of the public entities into four groups. The first one is formed by the northern and northeast states, with the exception of Paraiba State. The second group brings together all the states of the southern and central-western region, in addition to Espírito Santo, Minas Gerais and Paraíba. The third group contains São Paulo, Rio de Janeiro. Finally, the fourth group, the last one, is formed by the Federal District suggesting that entities located in the same region may have more similar characteristics in terms of socioeconomic characteristics and itsdisclosure index. The results allowed the identification of the explanatory characteristics of the disclosure index according to the changes introduced by the NBCASP. Thus, it can be concluded that, for the public entities analyzed, size is positively associated with ID in agreement with the theoretical statement